1990
DOI: 10.1016/1044-0305(90)85051-m
|View full text |Cite|
|
Sign up to set email alerts
|

Improving fast atom bombardment mass spectra: The influence of some controllable parameters on spectral quality

Abstract: The relative effects of adjustable fast atom bombardment (FAB) parameters (choice of matrix, primary atom flux, and primary atom energy) on the appearance of FAB spectra (including signal-to-noise, signal-to-background, and signal-to-matrix ratios) of several organic dyes have been investigated. Beam-induced chemical damage is minimized by lowering the primary atom flux, by raising the primary atom energy, and by selecting a matrix with radical scavenging properties (e.g., m-nitrobenzyl alcohol). The relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Instrumental parameters associated with the FAB/LSIMS source conditions may also play an im-portant role in determining the extent of reduction observed. Those parameters that have been studied include time of irradiation [8,14,16,17,23]; primary beam energy [15,20,28); and bombarding beam density (flux) [12,15,20,23,28]. Wirth et al [8] observed a time dependence in their FAB analysis (Xe O primary beam) of azo-group-eontaining peptides.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Instrumental parameters associated with the FAB/LSIMS source conditions may also play an im-portant role in determining the extent of reduction observed. Those parameters that have been studied include time of irradiation [8,14,16,17,23]; primary beam energy [15,20,28); and bombarding beam density (flux) [12,15,20,23,28]. Wirth et al [8] observed a time dependence in their FAB analysis (Xe O primary beam) of azo-group-eontaining peptides.…”
mentioning
confidence: 99%
“…The primary beam density, however, plays a more important role in determining the extent of reduction. An increase in the beam density caused substantial increases in the enhancement ratios measured for methylene blue [20,30] and for different peptide systems [281. For systems in which the extent of reduction is large, therefore, it is more important to lower the primary beam density than it is to raise the primary beam energy [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 + H ' + 2 (5) a + H'-+[M + 11' ' (6) 1 + H + -* [M + 11" The electrochemical reduction of a to the leucomethylene blue, 2, is a two electron process (reactions (I) and (2)). If a similar reduction occurs as a result of the bombardment process, the subsequent protonation that there must be pathways to the two reduced species which are parallel rather than consecutive.…”
Section: Solutionmentioning
confidence: 99%